A Study of the Effects of Mobile Technology Solutions on Effective Deployment of Mobile Learning in Medical Education Based on the Technology Acceptance Model - Mohammad Reza Ardalan; Siroos Ghanbari; Fakhrossadat Nasiri; Iman Karimi (Kerman University of Medical Sciences, 2016)
Background & Objective: Mobile learning as a new stage of development in elearning provides opportunities for information transfer and strengthening and improving lifelong learning in students of medical sciences The present study was conducted to evaluate the effect of mobile technology solutions on effective deployment of mobile learning in medical education based on the Technology Acceptance Model (TAM) Methods: This was an objectivebased applied research and based on the method of data collection a descriptive survey The statistical population consisted of all faculty members of the Hamadan University of Medical Sciences in 2014 The sample size (n = 188) was determined using Cochran formula Data were collected using the Mobile Technology Development Strategies Questionnaires and Davis TAM Data analysis was performed using the correlation coefficient ttest confirmatory factor analysis structural equation modeling and path analysis and LISREL and SPSS software Results: Instructional strategies administrativestructural managerial and motivational-recreational respectively had the most significant effect (at the level of 001) on the teachers perception of the usefulness of mobile learning and the simplicity of its use Based on TAM these two components had positive effects on attitude toward using and deciding to use mobile technology Thereby they have significant positive effects on the application of mobile technology in teaching and learning by teachers (at the level of 001) Conclusion: Based on these results TAM was approved according to the guidelines provided on mobile learning development in the study population and thus has deployment potential in the target population